2005
DOI: 10.1111/j.0022-1112.2005.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Movement and mortality of stocked brown trout in a stream

Abstract: The movement and mortality of stocked brown trout Salmo trutta were investigated using radio telemetry. Four brown trout left the study area whereas the remaining fish were stationary. After 5 weeks, 13 out of 50 tagged brown trout were still alive in the stream. Surviving fish had a significantly lower mean movement per day than fish, which later either died or disappeared. This difference in behaviour was most pronounced 2 to 8 days after release. Predation by the otter Lutra lutra was probably the main caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 29 publications
5
51
0
Order By: Relevance
“…The dispersion of stocked brown trout is relatively well documented in the literature and, similarly to the present study, distinct individual movements were also found including stationary (maintaining the position near the stocking site) and mobile (ranging from upstream to downstream migrations) behaviour in the same stocked trout population (Cresswell, 1981). For example, Aarestrup et al (2005) found that four brown trout left the study area whereas the remaining fish (n= 46) were stationary. However, in our study it was observed a decline in the water flow that conditioned the potential displacement of fish during the radiotelemetry study (32 days).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The dispersion of stocked brown trout is relatively well documented in the literature and, similarly to the present study, distinct individual movements were also found including stationary (maintaining the position near the stocking site) and mobile (ranging from upstream to downstream migrations) behaviour in the same stocked trout population (Cresswell, 1981). For example, Aarestrup et al (2005) found that four brown trout left the study area whereas the remaining fish (n= 46) were stationary. However, in our study it was observed a decline in the water flow that conditioned the potential displacement of fish during the radiotelemetry study (32 days).…”
Section: Discussionsupporting
confidence: 84%
“…Poor stocked brown trout survival rates were also reported in several studies (Pedersen et al, www.intechopen.com 2003; Aarestrup et al, 2005). The significant decrease in the condition of stocked brown trout suggested a lower ability to explore the available resources.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Radio-tracking studies of rainbow trout, brown trout, bulltrout (Salvelinus confluentus), and cutthroat trout (Oncorhynchus clarki) under natural flow regimes are consistent in their findings that individual trout tend to remain in a small home area, generally <1 km, during non-spawning periods (Clapp et al 1990;Young 1996Young , 1998Knouft and Spotila 2002;Ovidio et al 2002;Schrank et al 2003;Aarestrup et al 2005;Popoff and Neumann 2005;Hojesjo et al 2007), but that they may move longer distances (e.g., 3-63 km) during migrations to spawning habitat (Bailey et al 1978;Meyers et al 1992;Brown and Mackay 1995;Swanberg 1997;Ovidio et al 1998;Burrell et al 2000;Hilderbrand and Kershner 2000;Meka et al 2003;Arnekleiv and Roenning 2004;Bahr and Shrimpton 2004;Bettinger and Bettoli 2004;Muhlfeld and Marotz 2005;Venman and Dedual 2005). In the South Fork American River rainbow trout would be expected to spawn in spring, as high winter flows recede.…”
Section: Discussionmentioning
confidence: 81%
“…All of the above studies and others have shown that there is a positive correlation between fish size and water depth, and that the larger the trout, the deeper water it prefers (Greenberg et al, 1996;Heggenes et al, 1999;Maki-Petays et al, 1997). This preference for deep water could be explained by the possibility that parr may primarily be feeding nocturnally during summer (Alvarez and Nicieza 2003;Orpwood et al, 2006;Conallin, 2009;Conallin et al, 2012), and seeking refuge during the day to avoid predation (Aarestrup et al, 2003;Gwiazda and Amirowicz, 2006). Parr in small Danish lowland streams are vulnerable to avian predators such as grey heron (Ardea cinerea) and great cormorants (Phalacrocorax carbo sinensis) (Aarestrup et al, 2003;Jepsen et al, 2010Jepsen et al, , 2013 which are common species in many European countries.…”
Section: Discussionmentioning
confidence: 80%